The Influence of Monoculture and Polyculture Planting Patterns on the Intensity of Pest Attacks by Helopeltis sp. on Arabica Coffee of the Sigarar Utang Variety in North Tapanuli Regency - Kuswardani, Retna Astuti; Mardiana, Siti; Suswati; Sihotang, Saipul (Jurnal Penelitian Pendidikan IPA, 2023)
Coffee is one of the leading commodities in the plantation subsector in North Sumatra which has good market opportunities both domestically and abroad. Especially in the Lake Toba area, apart from the PBKo pest, it turns out that attacks by the coffee leaf sucking pest Helopeltis sp. are also felt to be very important by farmers, because the presence of Helopeltis sp. This causes the coffee leaf shoots to develop brown spots, curl and eventually dry out and die (die back). The aim of the research was to study the symptoms of attacks and the intensity of Helopeltis sp. attacks on Arabica coffee plants in the Lake Toba area, North Tapanuli Regency. This research was carried out on people's coffee plantations in North Tapanuli Regency at an altitude of 1,300 meters above sea level, from February to June 2023. On the Sigarar Utang variety Arabica coffee plantation with monoculture and polyculture planting patterns. The sample plants were determined to be 10% of the total plants at each observation location. Sampling of plant samples is determined using a zig zag line. The parameters observed were the intensity of attacks and the percentage of pest attacks. The results obtained by Helopeltis sp. sucking shoot pests have been known to attack coffee plants in North Tapanuli Regency with symptoms of attack. At the start of the attack, leaf spots are visible, brown, curly and eventually dry out, die back, then grow rosettes, namely shoots, new ones that are shortened tightly and do not develop. The intensity of attacks by Helopeltis sp. on smallholder coffee plantations in North Tapanuli Regency is quite varied, from light to heavy attacks with the intensity of shoot attacks ranging from 15.67% to 57.80%. Monoculture coffee plantations with protective plants, but no pruning, are locations with Helopeltis sp. attack levels in the heavy category with shoot attack intensity reaching 56.66%. The intercropping coffee plant cultivation system (polyculture) had a significant influence on the low intensity of Helopeltis sp. attacks, where tcount (8.921) > ttable (2.306).